Angiotensin converting enzyme intron 16 insertion/deletion genotype is associated with plasma C-reactive protein concentration in uteroplacental dysfunction. (June 2015) - Häupl, Thomas; Zimmermann, Mathias; Kalus, Ulrich; Yürek, Salih; Koscielny, Jürgen; Hoppe, Berthold
Introduction: Disturbance of the uteroplacental circulation (UPC) and the renin-angiotensin system are involved in the pathogenesis of preeclampsia. In women with history of preeclampsia persistently elevated C-reactive protein (CRP) levels have been described. The angiotensin-converting enzyme (ACE) intron 16 insertion/deletion (I/D) genotype is associated with ACE activity and assumed to be a risk factor for preeclampsia. As ACE generates proinflammatory angiotensin II, we analysed, whether ACE intron 16 I/D genotype is associated with CRP and whether this association exhibited a relation to uteroplacental dysfunction. Materials and methods: A total of 639 women have been followed during pregnancy with repeated measurements of CRP levels (observations: n =2333). ACE intron 16 I/D genotype was determined, and its association with CRP was assessed with adjustment for non-independent observations. Results: CRP levels of ACE D allele carriers were significantly higher than those of the ACE II (wild-type) genotype ( p =0.0003, p adj =0.04). This relation was allele-dose dependent ( p <10 −4, p adj <0.02). Association between ACE I/D and CRP was significantly restricted to patients presenting with impaired UPC in univariate ( p <0.04) and multivariate analyses ( p =0.01). Conclusions: The ACE I/D genotype is significantly associated with CRP elevations during pregnancies complicated by disturbed UPC. Whether this effect on CRP is involved in pathogenesis of preeclampsia has to be elucidated.